North-South Trade, Technology Diffusion and Productivity Growth: Are Small States Different? - Maurice Schiff; Yanling Wang (Global Labor Organization (GLO), 2017)
The economies of small developing states tend to be more fragile than those in large ones. This paper examines this issue in a dynamic context by focusing on the impact of education and North-South trade-related technology diffusion (NRD) on TFP growth in small and large states in the South. The main findings are: i) TFP growth increases with NRD, education and the interaction between the two; ii) the impact of NRD, education and their interaction on TFP growth in small states is over three times that for large countries; and iii) the greater TFP growth loss in small states has two brain drain-related causes: a substantially greater sensitivity of TFP growth to the brain drain, and brain drain levels that are much higher in small than in large states.
Keywords: F22; J61; 330; Technology Diffusion; Trade; Productivity Growth; Education